MODEL PELATIHAN BERBASIS KOMPETENSI BAGI MANAJER ACCOUNT OFFICER (AO) (STUDI DI BANK BADAN USAHA MILIK DAERAH (BUMD) DI JAWA BARAT) - Kusumastuti, Dyah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
The purpose of this resarch is to find the competencies that predict to lead to an effective performance for Account Officer (Funding Sales) managers and that AO can be developed through these competencies. Research Methodology use sample AO managers that average and superior performance at a government bank which numbered 40 in West Java. Data was collected by questionnaire ordinal of competence and questions about the need for technical competence. Respondents were shown a selection of the level of competence and technical competence. Then the data is processed by classifying AO average and superior performance, furthermore use statistically test with Mann-Whitney test. Research Finding that there are eight competencies that differentiate AO average and superior performance, namely: Achievement Orientation, Information Seeking, Relationship Building, Problem Solving, Self Confidence, Organization Commitment, Communication and Flexibility. The implications of this research could be used for development & training AO, through Competencies are means of ensuring that an organization’s investment in her people supports the achievement of strategic goals. They can be used to hire the best available people, align behaviour with organizational strategies and values. Keywords: Competency, Superior Performance, Training